Prevalence and outcome of neonatal tetanus in Zaria, Northwestern Nigeria - Richard Onalo; Hassan Mshalia Ishiaka; Williams Nuhu Ogala (Journal of Infection in Developing Countries)
Introduction: Neonatal tetanus is a highly debilitating disease with high mortality. Global efforts at eliminating the disease in developing countries are yielding results but slower than expected. The high case fatality of neonatal tetanus remains a therapeutic challenge to physicians and requires continuous evaluation. This study aimed to determine the incidence and outcome of neonatal tetanus in Zaria, northwestern Nigeria.